DIGNITY AT WORK: WHY IS INTERNATIONAL LAW FIT FOR THE JOB? - Lafond, Geneviève (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2011)
This article aims to demonstrate that despite the international community’s best efforts to eradicate slavery and slavery-like practices, such as forced labour, these phenomenons are still on the rise today. It will be shown that sweatshop conditions, in the worst of cases, fit the definition of modern forms of slavery and slavery-like practices. Moreover, it will be demonstrated that voluntary measures adopted by multinational corporations are insufficient and more coercive measures need to be taken. Indeed, as submitting workers to sweatshop conditions can amount to the committing of an international crime, corporations and Corporate Executive Officers engaging in these practices should be prosecuted for doing so. This article seeks to demonstrate that the eradication of sweatshops could be achieved by using concepts developed by international criminal law. Additionally, other countries could adopt national measures (like the U.S.A.’s ATCA and RICO) in order to avoid problems raised by corporate structure, as well as adequately compensate the victims of sweatshop labour.